NMR Imaging of the Spine - Han, Jong S.; Kaufman, Benjamin; El Yousef, Saba J.; Benson, Jane E.; Bonstelle, Charles T.; Alfidi, Ralph J.; Haaga, John R.; Yeung, Hong; Huss, Richard G. (American Journal of Neuroradiology, 1983)
The usefulness of nuclear magnetic resonance (NMR) images in the evaluation of spinal disorders below the craniocervical junction was studied. Six normal subjects and 41 patients with various spinal abnormalities were examined. NMR proved capable of demonstrating important normal and pathologic anatomic structures; it was useful in the evaluation of syringohydromyelia and cystic spinal cord tumors, and the bright signal intensity of lipoma was quite impressive. In the evaluation of herniated disk, NMR images offered a new perspective by visualizing abnormal degradation of the signal intensity of the nucleus pulposus itself. NMR images were least valuable in the evaluation of spondylosis and spinal stenosis. Although NMR imaging of the spine is still in a very early developmental stage, the absence of both ionizing radiation and risks associated with contrast material makes it especially attractive as a new diagnostic method. This limited experience with currently available equipment suggests that, with technical refinement, the efficacy of NMR of the spine will increase.